Dual Conversations: Body Talk Among Young Women and Their Social Contacts - O’Dougherty, Maureen (2011)
In this article, we explore an area little researched within the literature on body dissatisfaction: the content and functions of body talk. We interviewed 60 diverse, college-educated women aged 18 to 30 in the urban United States about how social contacts talked about their bodies. Half the women, and by their reports, half their contacts (N = 295) endorsed some ideal body, most often the thin model. The other half favored a “healthy,” “average” range in body size, shape, and/or appearance. Excepting family members, contacts gave mostly positive comments about women’s bodies or appearance, or made no comments. Many critiqued their own bodies, however, as did nearly half the women participants. We suggest that these women exempted others, but not themselves, from critical body surveillance, rendering contestation of the ideal theoretical. We also suggest that the parallel airing of self-criticism repeatedly circulated through speech, if not through practice, the imperative to regulate one’s own gendered body toward unattainable normativity.